Fabrication of a 2D thermally tunable reflective grating for measuring a CO2 laser beam profile - Riahi, Mohammadreza; Latifi, Hamid (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
In this article, application of a 2D thermally tunable reflective grating for measuring the beam profile of a CO2 laser is proposed. A 2D grating is first fabricated on a glass substrate by conventional lithography technique. The grooves of the grating are filled with nitrobenzene, the refractive index of which highly depends on temperature. A double side polished silicon wafer is then placed on the grating. If a CO2 laser is incoming from silicon side, a portion of it is transmitted and absorbed in the grating structure. Depending on the beam profile of the CO2 laser, a temperature profile is produced on the grating causing the same profile for efficiency of the grating for a visible light. The changes in the efficiency, cause changes in intensity of dif-fraction orders. By measuring the intensity of the first order of diffraction, the beam profile of the CO2 laser is imaged on a visible CCD camera.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 735-742
Keywords: optyka; tunable grating; laser beam profiler